ANALYSIS OF THE DEVELOPMENT TRENDS OF THE GLOBAL FINTECH MARKET - Vagner , Iryna; Kundrya-Vysotska , Oksana; Demko , Iryna (Socio-economic relations in the digital society, 2021)
Abstract. One of the promising ways of economic growth of enterprises is their innovative development. The twenty first century is marked not only by the development of science and technology but also by the emergence and growth of the FinTech services market. The global financial crisis of 2008 triggered global changes in the financial services market, due to the spread of digital technologies, reduced confidence in the usual financial intermediaries in the post-crisis period, and changes in customer priorities for speed, availability, and ease of obtaining financial services. Therefore, modern conditions determine the relevance of the study of the financial services market, taking into account the emergence of FinTech innovations. The aim of the study is to generalize the theoretical foundations of the formation and development of recommendations for the impact of FinTech innovations on the development of domestic and foreign enterprises in the context of globalization. The research was aimed at analyzing the history of development and key factors that influenced the formation of the FinTech market. The article uses the results of a large-scale survey of more than 22,000 Internet users in 20 countries, conducted in 2017 by Ernst & Young. According to this survey, it was found that more than 33 % of users are active users of Fintech services, which allowed us to analyze the stages of formation of the FinTech market to date. A study on the impact of the COVID-19 pandemic has been conducted regarding the growth of the FinTech market in the world and an analysis of the main trends in the development and promotion of the global fintech market in the first quarter of 2021. The main trends of FinTech market development in Ukraine and the world for the period 2021—2023 are highlighted. Significant growth of investments in the FinTech market and globalization of processes in the industry: mergers, integration into the ecosystem, and assimilation of know-how into traditional banking allow us to conclude that the current generation of customers continues to avoid traditional financial institutions or abandon them in favor fully digital banks and embedded financial services. In response, traditional financial institutions are trying to compete, increasing the pace of innovation and digitalization in various ways, which will continue in 2021—2023. Given all these processes, the increase in the number of investments in the financial and technical sector and the rapid growth of this segment is irreversible. in turn, needs further thorough research. Keywords: FinTech market, digital payments, investments, mega-rounds, Blockchain, D2C (direct to client), Insurtech acceleration, Regtech. JEL Classification G17, O32, O33 Formulas: 0, fig.: 1; tabl.: 3; bibl.: 19.